STRATEGI PENINGKATAN KINERJA GURU MELALUI MANAJEMEN KOMPETENSI DI SMPN 20 SURABAYA - Wulandari, Retno; Cahyanti, Adelia Nasha Fitri; Windasari, Windasari; Cindy, Agustin Hanivia (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2024)
This research aims to identify strategies for improving teacher performance through competency management. The research method used is literature study to collect the latest information regarding competency management and teacher performance. The analysis found that teacher performance can be improved through various strategies, such as holding training/workshops. Effective competency management is also needed to identify teacher training and development needs and manage competencies in line with curriculum needs and pedagogical developments. It is hoped that the results of this research can contribute to the development of competency management policies and practices to improve teacher performance.